IDMP-based Fast Handoffs and Paging in IP-based Cellular Networks - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2001)
We consider the use of our previously proposed Intra-Domain Mobility Management Protocol (IDMP) in fourth-generation mobile networks. On evaluating the heterogeneous access technologies, cellular layouts, and application characteristics of 4G environments, we realize a need to reduce both handoff latency and the frequency of mobility-related signaling. We first present IDMP's fast intradomain handoff mechanism that uses a duration-limited proactive packet multicasting solution. We quantify the expected buffering requirements of our proposed multicasting scheme for typical 4G network characteristics and compare it with alternative IP-based fast handoff solutions. We also present a paging scheme under IDMP that replicates the current cellular paging structure. Our paging mechanism supports generic paging strategies and can significantly reduce the mobility-related IP signaling load